New developments in the management of hepatitis C virus infection: focus on boceprevir - Berenguer M (Dove Medical Press, 2012)
Marina Berenguer,1–3 F Xavier López-Labrador4–61Hepatology-Liver Transplantation Unit, Digestive Medicine Service, Hospital Universitari La Fe, Valencia, Spain; 2Department of Medicine, University of Valencia, Valencia, Spain; 3CIBERehd, Instituto de Salud Carlos III, Madrid, Spain; 4CSISP, Center for Public Health Research, Public Health Department, Generalitat Valenciana, Valencia, Spain; 5Microbiology Department and Institut Cavanilles, University of Valencia, Valencia, Spain; 6CIBEResp, Instituto de Salud Carlos III, Madrid, SpainAbstract: Chronic hepatitis C virus infection is an important public health problem, and the standard treatment (combination of pegylated interferon-α and ribavirin) has an effectiveness rate of only 40%–50%. Novel virus-specific drugs have recently been designed, and multiple compounds are under development. The approval for the clinical use of direct-acting antivirals in 2011 (boceprevir [BOC] and telaprevir, viral NS3 protease inhibitors) has increased recovery rates by up to 70%. Therefore, a highly effective treatment has been envisioned for the first time. This paper focuses on BOC and the implementation of new BOC-based treatment regimes.Keywords: HCV, antiviral therapy, protease inhibitors, viral resistance